The composition and oxidative stability of vegetarian omega‐3 algal oil nanoemulsions suitable for functional food enrichment. (23rd November 2019) - Lane, Katie E; Zhou, Qiqian; Robinson, Sharon; Li, Weili
Abstract: BACKGROUND: Long chain omega‐3 polyunsaturated fatty acid (LCn3PUFA) nanoemulsion enriched foods offer the potential to address habitually low oily fish intakes. Nanoemulsions increase LCn3PUFA bioavailability, although they may cause lipid oxidation. The present study examined the oxidative stability of LCn3PUFA algal oil‐in‐water nanoemulsions created by ultrasound using natural and synthetic emulsifiers during 5 weeks of storage at 4, 20 and 40 °C. Fatty acid composition, droplet size ranges and volatile compounds were analysed. RESULTS: No significant differences were found for fatty acid composition at various temperatures and storage times. Lecithin nanoemulsions had significantly larger droplet size ranges at baseline and during storage, regardless of temperatures. Although combined Tween 40 and lecithin nanoemulsions had low initial droplet size ranges, there were significant increases at 40 °C after 5 weeks of storage. Gas chromatograms identified hexanal and propanal as predominant volatile compounds, along with 2‐ethylfuran, propan‐3‐ol and valeraldehyde. The Tween 40 only nanoemulsion sample showed the formation of lower concentrations of volatiles compared to lecithin samples. The formation of hexanal and propanal remained stable at lower temperatures, although higher concentrations were found in nanoemulsions than in bulk oil. The lecithin only sample had formation of higher concentrations of volatiles at increased temperatures, despite having significantly larger droplet size ranges than the other samples. CONCLUSION: Propanal and hexanal were the most prevalent of five volatile compounds detected in bulk oil and lecithin and/or Tween 40 nanoemulsions. Oxidation compounds remained more stable at lower temperatures, indicating suitability for the enrichment of refrigerated foods. Further research aiming to evaluate the oxidation stability of these systems within food matrices is warranted. © 2019 Society of Chemical Industry